PENGARUH SUPERVISOR SUPPORT, WORK FAMILY CONFLICT, DAN JOB STRESS TERHADAP KINERJA DOSEN FAKULTAS EKONOMI DAN BISNIS (FEB) UNIVERSITAS WIJAYA PUTRA SURABAYA - Naura Arisanti Chairina; Muzakki Muzakki (Jurnal Ekonomi, Bisnis dan Social, 2024)
The purpose of this study was to analyze the parcial and simultaneous effect of supervisor support, work family conflict, and job stress on the performance of lecturers of the Faculty of Economics and Business (FEB) at Wijaya Putra University Surabaya. The data analysis method used in this study is multiple linear regression analysis. The second method of analysis is to use multiple coefficients of determination. This type of research is a type of explanatory research. The object of research is a lecturer at the Faculty of Economics and Business (FEB) at Wijaya Putra University Surabaya. Based on the results of the analysis shows that supervisor support has a significant negative effect on the performance of lecturers at the Faculty of Economics and Business (FEB) at Wijaya Putra University Surabaya. Based on the results of the analysis, it shows that job stress has a significant negative influence on lecturer performance.